SPREAD DAN STRUKTURNYA SERTA DAMPAKNYA TERHADAP STOCK RETURN DI BURSA EFEK INDONESIA - Purba, Saut; Silalahi, Donalson (UNIKA Santo Thomas, 2014)
The research on the influence of bid ask spread on the stock return has been widely applied. Some of these research indicates that spread has a positive and significant effect on the stock return and the other research show that spread has a negative and significant effect on the stock return. Referring to the results of these studies, the purpose of this research is to explain why the relationship of spread and stock return is not consistent. The study was conducted at the Indonesia Stock Exchange between the year 2007 and 2008 with the sample size 1.707 observations. In this study, first done decomposition of spread to information friction and real friction. Based on the decomposition of spread, further the component of information friction and real friction associated with the stock return. The results of the research showed that the component of information friction has a positive and significant effect on the stock return. Furthermore, the component of real friction has a negative and significant effect on the stock return. Therefore, the inconsistency coefficient direction of the influence of spread on the stock return caused components of the spread. Furthermore, the results showed that the stock return are highly sensitive to the changes of information friction